Answer:
x = -1 ± √(10/3) = (-3 ± √30)/3
Explanation:
Steps to complete this process:
ax² + bx + c = 0
- Divide by the co-efficient of x² i.e. 'a'
=> (ax² + bx + c)/a = 0/a
=> x² + (b/a)x + (c/a) = 0
=> x² + 2x(b/2a) + (c/a) = 0
Now it seems somewhat like a square (x² + 2x(b/2a), in order to complete:
- Add (b/2a)² to both sides
=> x² + 2(b/2a) + (b/2a)² + (c/a) = (b/2a)²
=> (x + b/2a)² + (c/a) = b²/4a²
=> (x + b/2a)² = (b² - 4ac)/4a²
So on & you can derive quadratic formula.
In the given question:
=> 6b² + 12b - 14 = 0
=> (6b² + 12b - 14)/6 = 0/6
=> b² + 2b - 7/3 = 0
=> b² + 2(1)b + 1² - (7/3) = 1²
=> (b + 1)² - (7/3) = 1
=> (b + 1)² = 10/3 or 30/9
=> b + 1 = ±√(30/9)
=> b = -1 ± √(30)/3
=> b = (-3 ± √30)/3
*this is the rationalized form(rational-denominator), exact answer:
=> (b + 1)² - (7/3) = 1
=> (b + 1) = ± √(10/3)
=> b = -1 ± √(10/3)
You can take LCM, and even rationalize it to (-3 ± √30)/3.